Maximizing me : 30 lessons on the the journey to self-empowerment - Cunningham, Hart, 1975- (Aslan Pub., 2007)
"A collection of thirty concise lessons based on the author's maxims for success in business and personal life. Urges discipline, determination and unified resolve in the pursuit of clear goals based on a long-range life plan. Each lesson is augmented by a short assignment"--Provided by publisher.